Parkinson’s disease and dopamine transporter neuroimaging: a critical review - Shih, Ming Chi; Hoexter, Marcelo Queiroz; Andrade, Luiz Augusto Franco de; Bressan, Rodrigo Affonseca (São Paulo Medical Journal, 2006)
Parkinson’s disease (PD) is a common neuro- degenerative disorder that is mainly caused by dopaminergic neuron loss in the substantia nigra. Several nuclear medicine radiotracers have been developed to evaluate PD diagnoses and disease evolution in vivo in PD patients. Positron emission tomography (PET) and single photon computerized emission tomog- raphy (SPECT) radiotracers for the dopamine transporter (DAT) provide good markers for the integrity of the presynaptic dopaminergic system affected in PD. Over the last decade, radiotracers suitable for imaging the DAT have been the subject of most efforts. In this review, we provide a critical discussion on the utility of DAT imaging for Parkinson’s disease diagnosis (sensitivity and specificity).